Single-Center Use of Prothrombin Complex Concentrate in Pediatric Patients - Karube, Takaharu; Andersen, Courtney; Tobias, Joseph D. (Journal of Pediatric Intensive Care, 2020)
Coagulation disturbances frequently occur in critically ill children. Four-factor prothrombin complex concentrate (4F-PCC) may have a potential role in managing these patients while avoiding concerns associated with fresh frozen plasma. However, data on this product in critically ill children is scarce. We retrospectively identified 24 critically ill pediatric patients who received 4F-PCC. The primary indication was to correct coagulopathy and control bleeding in the trauma or surgical setting. 4F-PCC effectively decreased the international normalized ratio level, a surrogate marker of hemostasis. Further study is warranted to identify efficacy, indications, optimal dosing, and adverse effects in the critically ill pediatric patients.
Keywords: prothrombin complex concentrate; pediatrics; coagulopathy